Pengembangan Pembelajaran Interaktif Dalam PJOK Berbasis Aplikasi Untuk Meningkatkan Motivasi Belajar Siswa - Ricky Darmawan; Akhmad Sobarna; Sumbara Hambali (Universitas Hamzanwadi, 2026)
Physical Education (PJOK) instruction in high schools in Tangerang Regency faces challenges such as conventional, teacher-centered methods; limited use of digital technology; inadequate facilities and infrastructure; and low student motivation (58% of students find the lessons boring). This study aims to develop an app-based interactive learning medium and to test its validity, practicality, and effectiveness in increasing students’ motivation to learn. The research method used the Borg and Gall Research and Development (R&D) model, with test subjects including 3 validation experts, 10 students in a small pilot group, 32 students in a large pilot group, and 12 Physical Education teachers. Data collection instruments consisted of questionnaires, while data analysis was conducted through validity, practicality, and effectiveness (N-Gain) tests, as well as a Paired Sample t-test. The results showed that the average expert validation percentage was 88.6% (highly acceptable), the response rate from the large-group test students was 90.25% (very good), and the response rate from teachers was 89.5% (very good). The average learning motivation score increased from 68 on the pretest to 85 on the posttest, with an N-Gain of 0.53 (moderate category). The Paired Sample t-test yielded a significance level of 0.000 (p < 0.05) with an effect size of 2.27 (large effect). In conclusion, the application-based interactive learning medium developed has been proven to be valid, practical, and effective in increasing the learning motivation of Physical Education students.